Corn Cost-Return Budget in North Central Kansas - O'Brien, Daniel M.; Duncan, Stewart R.; Ibendahl, Gregg (My University, 2015)
This publication provides estimated cost and returns for forward farm planning for corn production in north central Kansas.
MF2161_2015_04
Keywords: MF2161; Crops; Economics; MF